Persistence and Metabolism of Folpet in Grapes and Wine - Cabras, Paolo; Angioni, Alberto; Garau, Vincenzo L.; Melis, Marinella; Pirisi, Filippo M.; Farris, Giovanni A.; Sotgiu, Carla; Minelli, Elizabeth V. [UNESP] (American Chemical Society (ACS), 1997)
The fate of folpet from the treatment on vine to the production of wine was studied. Sunlight degraded folpet to unknown products. Phthalimide was a minor metabolite formed on grapes from folpet. Folpet degraded in must, giving 80% phthalimide; the results obtained with model solutions showed that in must folpet can also give small amounts of phthalic acid. During wine-making folpet degraded completely, and at the end of fermentation phthalimide was only present in wine. This compound was stable in wine after several months. The presence of folpet in grapes inhibited the alcoholic fermentation of Saccharomyces cerevisiae and Kloeckera apiculata completely. Phthalimide, on the contrary, had no negative effect on the fermentative action of the two yeasts. GC and HPLC methods were developed to determine folpet and its metabolites.
Keywords: Folpet; Grapes; Metabolites; Residues; Wine